Effects Of Play-Based Circuit Training On Locomotor Skill Development In Preschool-Aged Children - Andi Amri Yahya; Awaluddin Awaluddin; Muh Ali Akbar (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2025)
Purpose This study aimed to examine the effectiveness of an integrated play-based circuit training model in improving locomotor movement skills among preschool-aged children. The need for structured and engaging physical activity models in early childhood education is increasingly recognized, especially given rising concerns over declining motor competence in young children. Materials and Methods A quasi-experimental design was employed involving 40 children aged 5–6 years, who were randomly divided into an experimental group (n = 20) and a control group (n = 20). The experimental group participated in an 8-week intervention combining circuit-based motor activities with playful elements, conducted three times a week. The control group engaged in routine unstructured physical activities. Pre-test and post-test assessments of locomotor skills were conducted using the Test of Gross Motor Development–2 (TGMD-2). Statistical analysis included paired and independent t-tests to evaluate within-group and between-group differences, respectively, with significance set at p < 0.05. Results: The experimental group demonstrated a statistically significant improvement in locomotor skills compared to the control group. Mean post-test scores increased more markedly in the experimental group, indicating the effectiveness of the integrated model in enhancing movement competence. Conclusions: The findings support the hypothesis that a play-based circuit training model is effective in improving locomotor skills in preschool-aged children. This approach offers a practical, enjoyable, and developmentally appropriate method for early childhood educators to support motor development. Future research should explore broader implementation and long-term impact on physical literacy